Realistic variations in substrate composition affect spawning preference and egg retention in river lamprey (Lampetra fluviatilis). Issue 4 (1st August 2022) - Daupagne, Léa; Dhamelincourt, Marius; Michaud, Anne; Rives, Jacques; Sebihi, Stellia; Tentelier, Cédric
Abstract: Egg drift from the nest is clearly an important cause of mortality in lithophilic species, but the effect of substrate composition on this process has been overlooked. Here, we investigated the role of substrate on the spawning preference and egg retention of river lamprey ( Lampetra fluviatilis ) during a whole breeding season in a two‐option experimental setting. Despite no initial preference, the lamprey eventually favoured the most efficient substrate for egg retention. The pebbly substrate hosted 12 times as many matings as the sandy one, while blurting 20% fewer eggs.